Optimal Allocation of PV and DSTATCOM for Enhancing the Power Quality of East Delta Egyptian Distribution Network - Adel A. Elbaset, Salah Kamel, Amal M. Abd El Hamed, Mohamed Ebeed, Montaser Abd El Sattar (International Journal of Advanced Science and Technology, 2019)
This paper determines the optimal sitting and sizing of photovoltaic (PV) generation units and Distribution Static Synchronous Compensator (DSTATCOM) in the real distribution network East Delta Network (EDN).  In the study using an efficient optimization algorithm called Ant lion optimizer (ALO) for enhancing the power quality of this network. The considered objective function is a multi-objective function which includes minimization of power losses, enhancement of voltage profile and improving the system stability considering the system equality and inequality constraints. The studied cases are presented in this paper including installation of PV units only, installation of DSTATCOMs only and installation of PV units along with DSTATCOMs. The simulation results reveal that, the objective function is enhanced considerably by installation of PV units along with DSTATCOMs compared to other cases. Moreover, the results verify the applicability and the effectiveness of ALO for determining the optimal locations and ratings of PV units and DSTATCOMs in this network.  Keywords: PV, DSTATCOM, Ant lion optimizer, Power losses, Radial Distribution system.